Remake/remix: Shakespeare’s code in Brothers Presnyakov’s works - Frolova, Anna (Przegląd Wschodnioeuropejski, 2018)
Art researchers of modern literature are connected with the classical heritage. The remake becomes one of the forms of the code conversion of classics, which gives context and allows the creation of “an expressive sociocultural portrait of our time”. The remix assumes a creation of the secondary work in a more modern option and often presents the “text pieces” rearranged in any order. In the modern literature process it is possible to note the paradoxical phenomenon when the same plot is portrayed by the same author twice. The Brothers Presnyakovs create works at an interval of five years with the identical name, “Playing the Victim”, but in different genres (the play and the novel). Texts are connected by special relations: they have a distinct subject similarity, an identical system of images and are united with their correlation to Shakespeare’s tragedy “Hamlet”. In this article, there is an attempt to understand why the authors readdress the mastered material and how the meanings of the universal language of classics based on absolute values are transformed.